ANALISIS POTENSI PAJAK RESTORAN DI KAWASAN WISATA ANYER KABUPATEN SERANG - Diana Indah Pertiwi; Evi Yulia Purwanti (Diponegoro Journal of Economics, 2014)
ABSTRACTAnyer Tourism Region as one tourist destination in Serang regency has a high potential to be developed. The existence of the restaurant tax is very important as a source of local revenue. Every year, the restaurant tax revenue is always improved and restaurant tax revenue also always meets the target set. The difference between realization restaurant tax revenues and restaurant tax revenues target indicates that the potential is not optimal.The purpose of this study is to analize the potential and effectiveness of the restaurant tax in Anyer Tourism Regions, Serang regency. The data is uses in this study are primary data and secondary data. Primary data includes the number of seats filled, crowded and less crowded period, turn over, average price, number of days in a year and amount of restaurant tax rates. The analytical method uses in this research is descriptive quantitative method and potentiality analize, effectiveness analize, and also pearson product moment correlation analize.The analize shows that the potential of the restaurant tax value is very large compared to the restaurant tax revenue realization. The gap shows that the actual potential is also very large, but local governments have less attention. Effectiveness of tax collection and the restaurant shows that the management of the restaurant tax in Anyer Tourism Regions ineffective. Product moment correlation analysis indicate the potential variables significantly influence the restaurant tax receipts taxes, but only restaurants are in the medium category.